African Elephant Specialist Group (AfESG)/ Groupe des Specialistes des Elephants Africain - Dublin, Holly (Pachyderm, 2000)
Reviews aspects of the facilitation which has gone on over the past six months including: a meeting in Cameroon which focused on cross border initiative regarding the conservation of forest elephant in Cameroon, CAR, Congo and Gabon, and training in MIKE for personnel in this region with particular emphasis on measuring law enforcement effort in the forest; the Human Elephant Conflict Taskforce accomplishments thus far; and the Fourth African Range States Dialogue which provided a forum for the nations involved to come to an agreement which they presented to COP11. Ongoing work is being done on the two monitoring systems MIKE and ETIS which will be implemented across the continent.